DAMPAK GAS RUMAH KACA ARANG TEMPURUNG KELAPA DENGAN METODE LIFE CYCLE ASSESSMENT (BATASAN SISTEM GATE-TO-GATE) - Tyara Puspaningrum; Mohamad Yani; Nastiti Siswi Indrasti; Chandra Indrawanto (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Charcoal is a coconut derivative product produced from burning coconut shells. In this study, coconut shell charcoal was obtained from the by-product of copra processing. The processing of coconut shell charcoal produces emissions that pollute the environment, which are greenhouse gas (GHG) emissions equivalent to CO2-eq. Life cycle assessment (LCA) is a method that can assess the environmental impact of a product throughout its life cycle. Net energy calculation was carried out to determine the energy efficiency of charcoal production in the form of net energy value (NEV) and net energy ratio (NER). The LCA studied was gate-to-gate, namely from coconut shell transportation to processing into charcoal with emission function units per 1 kg of coconut shell charcoal product. The study was conducted at CV X, located in Sukabumi, West Java, Indonesia. The calculation results show that the raw material transportation stage produced 0.0626 kg CO2-eq/kg charcoal, while the pyrolysis stage produced 0.212 kg CO2-eq/kg charcoal. Energy efficiency analysis showed NEV 9,398.66 MJ and NER 1.09. Recommendations for improvement that can be given are to produce charcoal in one place with a copra factory and produce liquid smoke from the combustion of charcoal. Charcoal production in one factory with a copra factory could reduce the GHG impact by 48%, increase NEV to 12,823.19 MJ, and increase NER to 1.13. Utilization of smoke into liquid smoke increased NEV and NEV to 107,715.75 MJ and 2.03. Combining the two scenarios increased NEV and NER to 211,856.62 MJ and 2.10. Keywords: coconut shell charcoal, life cycle assessment, net energy ratio, net energy value